THE EFFECTIVENESS OF ECONOMIC TEXTBOOK BASED ON 5.0 USING WORDPRESS FOR FIRST GRADE OF SMA 1 KOTA SALAK DHARMASRAYA (JURNAL ECONOMICA : Research of Economic And Economic Education, 2022)
This research is motivated by the needs of students in developing online-based textbooks with more interesting learning resources. The purpose of this research is to develop a wordpress website-based textbook as an online learning resource that can be used in the learning process. then another goal is how student learning outcomes using online-based learning resources. This type of research is the development of wordpress-based textbooks using the ADDIE model. Where there are five stages, namely the stages of analysis, design, development, implementation and evaluation. Validation questionnaires, practicality questionnaires, effectiveness questionnaires and student learning outcomes assessments were used to assess product feasibility. For the validation questionnaire, 6 other people were used, consisting of 2 economics teachers, material experts, 2 economics lecturers as media experts, and 2 language lecturers as linguists. Meanwhile, the effectiveness assessment carried out an assessment of the activeness of class XI III students spread over 3 locales. And for learning outcomes, an assessment of the test questions given to students is carried out. Based on the results of the analysis of the effectiveness assessment of Economics Subject learning tools using the WordPress website media at SMA Negeri 1 Koto Salak which was assessed by 30 students, the most students answered very effectively (90%) and as many as (10%) students stated effective. This shows that students understand well and easily learn economics textbooks using WordPress website media.